Methodology for Conducting Practical Exercises to Study the Simulation System 3DS Max 2020 (Texas Journal of Engineering and Technology, 2022)
In this article, you can familiarize yourself with the methodology for conducting practical exercises on studying the 3Ds Max 2020 modeling system. The program also explains the lines from specific objects that will be used.